2013
DOI: 10.1099/jmm.0.063032-0
|View full text |Cite
|
Sign up to set email alerts
|

Complex interactions of Klebsiella pneumoniae with the host immune system in a Galleria mellonella infection model

Abstract: Worldwide, Klebsiella pneumoniae is an increasingly problematic opportunistic pathogen, with the emergence of carbapenem-resistant isolates of special importance. The mechanisms of virulence are poorly understood, and the current study utilized the invertebrate model Galleria mellonella to investigate facets of the virulence process. A range of UK clinical isolates and reference strains was assessed in Galleria by measuring survival as an end point. The clinical strains showed a range of virulence, with the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 44 publications
1
45
0
2
Order By: Relevance
“…The mechanism underlying the pronounced virulence of ST69 isolates in this model has not yet been determined. Previous work has correlated growth rate with lethality in G. mellonella , where mortality was associated with proliferation of Burkholderia species, Klebsiella pneumoniae , Staphylococcus aureus or Streptococcus pneumoniae within the larvae [19],[21],[40],[41]. However, we investigated growth rate in LB medium and the ST69 isolates we have examined here were in fact seen to have the slowest growth rate, or longest doubling time (data not shown).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…The mechanism underlying the pronounced virulence of ST69 isolates in this model has not yet been determined. Previous work has correlated growth rate with lethality in G. mellonella , where mortality was associated with proliferation of Burkholderia species, Klebsiella pneumoniae , Staphylococcus aureus or Streptococcus pneumoniae within the larvae [19],[21],[40],[41]. However, we investigated growth rate in LB medium and the ST69 isolates we have examined here were in fact seen to have the slowest growth rate, or longest doubling time (data not shown).…”
Section: Resultsmentioning
confidence: 79%
“…The larvae of the wax moth Galleria mellonella have been used as an infection model to describe and evaluate microbial pathogenicity for a number of bacterial pathogens, including enteropathogenic E. coli (EPEC) [15][19]. The virulence mechanisms of many pathogens in G. mellonella show a high degree of similarity to mammals, including humans [20],[21].…”
Section: Introductionmentioning
confidence: 99%
“…End points in G. mellonella infection models include survival rate, which can be assessed up to 5 d post infection, or longer with some fungal pathogens, facilitating the calculation of a maximum half lethal dose (LD50); expression of antimicrobial proteins in response to infection; production of lactate dehydrogenase as a marker of cell damage and biophotonic imaging to measure proliferation of bioluminescent microorganisms responsible for larval infection. [33][34][35][36][37] A pathological scoring system was recently proposed by Loh et al 38 in which an assessment of larval mobility, cocoon formation, melanisation and survival was used to assess larval health.…”
Section: G Mellonella To Study Toxinsmentioning
confidence: 99%
“…The assessment of bacterial burden in larval haemolymph may prove useful for increasing the assay's sensitivity. 15 Thus, these data indicate that the G. mellonella-K. pneumoniae infection model can be used to study the efficacy of antibacterial agents and, importantly, may provide a more simplistic system than mammalian models. 16 Although the G. mellonella infection model cannot replace well-established in vivo experimental models, it could be of use, and less expensive, for the evaluation of the efficacy of drugs against K. pneumoniae.…”
mentioning
confidence: 97%
“…5 McLaughlin et al 14 quantified the clinical virulence of K. pneumoniae producing carbapenemase K. pneumoniae with a G. mellonella model. Wand et al 15 reported that G. mellonella is a useful model for assessing factors that contribute to K. pneumoniae virulence.…”
mentioning
confidence: 99%